2020
DOI: 10.1039/d0ra00134a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electrical-hydrothermal aging degradation on dielectric and trap properties of high temperature vulcanized silicone rubber materials

Abstract: In this paper, a new aging platform combined the high voltage electric field and the hydrothermal environment was built.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The synergistic effect of UV light, salt, fog, humidity, acid rain and heat on the performance of silicone rubber and its composites was reported by Khattak et al [21]. The hydrophobicity recovery phenomenon of both RTV and HTV silicone rubber under different stresses was investigated in various studies, implying that the transfer of Low Molecular Weight (LMW) components from material bulk to the surface is the main reason for the recovery of hydrophobicity of silicone rubber [22][23][24][25]. Ahmadi-veshki et al concluded that pollution and humidity increased the probability of occurrence of flashover [26].…”
Section: Introductionmentioning
confidence: 93%
“…The synergistic effect of UV light, salt, fog, humidity, acid rain and heat on the performance of silicone rubber and its composites was reported by Khattak et al [21]. The hydrophobicity recovery phenomenon of both RTV and HTV silicone rubber under different stresses was investigated in various studies, implying that the transfer of Low Molecular Weight (LMW) components from material bulk to the surface is the main reason for the recovery of hydrophobicity of silicone rubber [22][23][24][25]. Ahmadi-veshki et al concluded that pollution and humidity increased the probability of occurrence of flashover [26].…”
Section: Introductionmentioning
confidence: 93%
“…(3) As for the high temperature vulcanization of SR, it also needs to be heated to 150 • C and kept for 2 h in processing [50].…”
Section: Light-curing Instead Of Heat-curing 221 Photocurable Process...mentioning
confidence: 99%
“…To the best of our knowledge, only a few researchers have taken on the challenge of building innovative multi-factor aging platforms for HTV-SR. Bi et al [15] analyzed the corona aging characteristics of SR under different humidity, salt fog, and haze conditions, demonstrating the facilitating role that humidity plays in the deterioration of SR. Hu et al [16] studied the aging mechanism of SR under both thermal and mechanical stresses, confirming the competitive and synergistic effects between the two stresses. Xu et al [17] established an aging platform combining an electric field and hydrothermal conditions for HTV-SR and discussed the failure law based on the trap theory. According to the studies above, high voltage, heat, and moisture are the most common factors for HTV-SR aging, whereby the setting of temperature is usually constant [18,19].…”
Section: Introductionmentioning
confidence: 99%